Reliability and validity of the Finnish version of the prosthesis evaluation questionnaire - Repo, Jussi Petteri; Piitulainen, Kirsi; Häkkinen, Arja; Roine, Risto Paavo; Kautiainen, Hannu; Becker, Paju; Tukiainen, Erkki Juhani (Disability and rehabilitation, 2018)
Thus far there have been no specific patient-reported outcome instrument in Finnish for health-related quality of life (HRQoL) assessment after major lower extremity amputation and successful prosthesis fitting. The prosthesis evaluation questionnaire (PEQ) was translated and cross-culturally adapted into Finnish. Participants completed a questionnaire package including the Finnish version of the PEQ and the 15 D HRQoL instrument. Scales (n = 10) were tested for internal consistency, floor-ceiling effect, and reproducibility for which participants completed the PEQ twice within a 2-week interval. Validity was tested by estimating the correlation between the 15 D index and the scales. The authors included 122 participants who had completed the questionnaire on two separate occasions in the final analysis. Mean scale scores of the 10 scales varied from 52 to 83. Cronbach's alphas ranged from 0.67 to 0.96. The total score showed no floor-ceiling effect. Reproducibility of the scales was good (intraclass correlation coefficient, 0.78-0.87; coefficient of repeatability, 19-36). Significant correlations were observed between the 15 D index and the scales for ambulation, social burden, usefulness, and well-being. This study provided evidence of the reliability and validity of the Finnish version of the PEQ in assessing the HRQoL among major lower extremity amputated patients who have been fitted with prosthesis. Implications for rehabilitation Measurement of quality of life during rehabilitation can provide important information on patients' well-being. The prosthesis evaluation questionnaire (PEQ) is a valid instrument for assessing health-related quality of life (HRQoL) after major lower extremity amputation. This study provided evidence of the reliability and validity of the Finnish version of the PEQ for assessing HRQoL among patient who have undergone major lower extremity amputation.